How to Simplify the Diagnostic Criteria of Metabolic Syndrome in Adolescents - Chun-Ming Ma; Fu-Zai Yin; Xiao-Li Liu; Rui Wang; Dong-Hui Lou; Qiang Lu (Pediatrics and Neonatology)
This study evaluated the feasibility and accuracy of the height-corrected definition for identifying metabolic syndrome (MS). Methods: In 2006, anthropometric and biochemical measurements were assessed in a cross-sectional population-based study of 3136 Han adolescents, aged 13–17 years. MS was defined according to the definitions of Cook et al, International Diabetes Federation, and the Society of Pediatrics, Chinese Medical Association. Waist-to-height and blood pressure-to-height ratios were alternatives to waist circumference and blood pressure in the height-corrected definition. Results: According to the MS definition and the height-corrected MS definition, this agreement would be classified as “very good” (National Cholesterol Education Program kappa coefficients: 0.850 in boys and 0.816 in girls; International Diabetes Federation kappa coefficients: 0.953 in boys and 0.807 in girls; Society of Pediatrics, Chinese Medical Association kappa coefficients: 0.932 in boys; p < 0.001) and “good” (Society of Pediatrics, Chinese Medical Association kappa coefficients: 0.737 in girls; p < 0.001). Conclusion: The present study demonstrates that the height-corrected definition of MS is a simple, inexpensive, and accurate tool for identifying MS in Han adolescents.